Aberrant waste disposal in neurodegeneration: why improved sleep could be the solution - Wafford, Keith A. (Cerebral circulation - cognition and behavior, 2021)
•Glymphatic clearance is an important feature of normal brain function.•Slow-wave sleep governs the optimal state of brain clearance.•Restoring sleep function could slow the process of neurodegeneration. Sleep takes up a large percentage of our lives and the full functions of this state are still not understood. However, over the last 10 years a new and important function has emerged as a mediator of brain clearance. Removal of toxic metabolites and proteins from the brain parenchyma generated during waking activity and high levels of synaptic processing is critical to normal brain function and only enabled during deep sleep. Understanding of this process is revealing how impaired sleep contributes an important and likely causative role in the accumulation and aggregation of aberrant proteins such as β-amyloid and phosphorylated tau, as well as inflammation and neuronal damage. We are also beginning to understand how brain slow-wave activity interacts with vascular function allowing the flow of CSF and interstitial fluid to drain into the body's lymphatic system. New methodology is enabling visualization of this process in both animals and humans and is revealing how these processes break down during ageing and disease. With this understanding we can begin to envisage novel therapeutic approaches to the treatment of neurodegeneration, and how reversing sleep impairment in the correct manner may provide a way to slow these processes and improve brain function.